Efektivitas Strategi Kampanye Pasangan Sherly Laos-Sarbin Sehe di Pilgub Maluku Utara: Kajian Media, Taktik, dan Mobilisasi Massa - Wahyuningtyas, Adela; Ramadhan, Makbul Wahid; Suprihono, Muhammad Barzany; Putranto, Algooth (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study analyzes the campaign strategy of the Sherly Tjoanda Laos and Sarbin Sehe pair in the 2024 North Maluku gubernatorial election with a focus on three main aspects, namely media, campaign tactics, and mass mobilization. This pair utilizes digital media such as TikTok and Instagram to reach young voters, as well as traditional media for groups of people who are less exposed to the internet. The campaign tactics they use include large-scale campaigns, personal approaches, public debates, and strengthening local cultural elements. Mass mobilization is carried out through large events and door-to-door approaches. The results of the analysis show that this strategy is effective in building emotional connections with voters, creating a positive image, and reaching various segments of society. The challenges in the form of negative campaigns are responded to with professionalism, prioritizing clarification of facts, and strengthening work programs. This study concludes that the combination of modern communication, personal approaches, and local adaptation are the keys to the success of their political campaign.